Degradation of bromate by Fe(II)Ti(IV) layered double hydroxides nanoparticles under ultraviolet light. (1st March 2019) - Xiao, Qian; Yu, Shuili; Li, Lei; Zhang, Yikui; Yi, Peng
Abstract: The photocatalytic decomposition of bromate (BrO3 − ), a possible human carcinogen, has attracted much attention because of its high efficiency and easier combination with ultraviolet (UV) disinfection in water treatment plants. In this study, the Fe(II)Ti(IV) layered double hydroxides (LDHs) have been made through a facile hydrothermal method and used as an alternative photocatalyst for reduction of BrO3 − . LDHs prepared at a Fe/Ti molar ratio of ∼0.5 and pH 7.0, denoted as FeTi-0.5 (pH 7.0), exhibited the highest BrO3 − removal efficiency (removal rate constant = 0.067 ± 0.002 min −1 ) compared to commercial TiO2 and the LDHs prepared at different pHs or different Fe/Ti ratios. The presence of alcohols in water enhanced the photocatalytic reduction of BrO3 − due to the greater abundance of electrons caused by alcohols effectively reacting with holes. The neutral pH also favors the degradation of BrO3 − . However, the presence of nitrate and nitrite can inhibit the degradation process, due to their reactions with hydrated electrons (eaq − ) and hydrogen atom radicals (H∙). Cyclic degradation runs and magnetic separation techniques demonstrated the superior reusability of the FeTi-0.5 (pH 7.0) LDH for BrO3 − removal. The removal rate of BrO3 − under UV was higher than that without UV, indicating that the decomposition proceeded primarily via a photo-reductive mechanism induced by eaq − and H∙ and thus degradation pathways are proposed. Moreover, when tested in tap water, greater than 90% of BrO3 − was removed after 60 min reaction in UV/FeTi-0.5 (pH 7.0) LDH systems in the presence of 5‰ (v/v) methanol. This demonstrates the high potential for such systems for removing BrO3 − from disinfected drinking water. This work may shed lights on the design of effective photocatalysts for the enhanced degradation of BrO3 − in water plants and the influence of constituents in raw water on the treatment. Highlights: FeTi-0.5 (pH 7.0) exhibited the highest BrO3 − decay rate and superior reusability. >90% of BrO3 − was reduced in tap and deionized water in 60 min in UV/FeTi LDHs systems. BrO3 − decay was enhanced in the presence of alcohols due to the efficient generation of electrons. BrO3 − was reduced to Br ‾ mainly by hydrated electrons and hydrogen atom radicals. Carbon dioxide and methyl formate were dominant carbon-containing products.